Container Media Test Information Sheet - Rao Mylavarapu; William d'Angelo; Nancy Wilkinson (EDIS)
Revised! SL-134, a 2-page illustrated fact sheet by Rao S. Mylavarapu, William d'Angelo, and Nancy Wilkinson, is the Container Media Test Form used by the UF/IFAS Extension Soil Testing Laboratory. The sheet provides details about how to collect samples and testing fees. Published by the UF Department of Soil and Water Sciences, February 2009.